Nudging in Healthcare - The Way to Higher Vaccination Rates? - Turányi, Samuel; Chytilová, Helena; Fidler, Armin; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2017)
This master thesis investigates impact of nudging on the level of vaccination rates against measles by utilizing insights from behavioral economics. In the theoretical part, brief overview of behavioral economics and its contributions to health economics is outlined. Additionally, direct application of nudging concepts and behavioral features in healthcare is illustrated, primarily focused on the vaccination issue. In the analytical part, two neighboring countries have been chosen for the research, Austria and Czech Republic and their regions Vorarlberg, Prague and South Bohemia. Their rates of vaccination based on data gathered from both private institutions as well as public sources were compared using documentary comparative analysis as a research method. Two hypotheses were set for testing: (1) Czech mandatory vaccination policy against measles had been historically more effective than Austrian opt-in system and (2) Choice architecture had profound effect on levels of coverage. None of the hypotheses was refuted. Research was narrowed down to examination of measles due to data availability. In final part, implications from findings were elaborated on. Subsequent policy recommendations were presented, referring to the type of vaccination system, incentives, behavioral as well as historical factors and concepts of nudging like peer pressure, framing, priming, loss aversion or three heuristics.
Vedoucí práce: Helena Chytilová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses